Dynamic Analysis of Cavitation Tip Vortex of Pump-Jet Propeller Based on DES - Jianping Yuan; Yang Chen; Longyan Wang; Yanxia Fu; Yunkai Zhou; Jian Xu; Rong Lu (Applied Sciences, 2020)
When a pump-jet propeller rotates at high speeds, a tip vortex is usually generated in the tip clearance region. This vortex interacts with the main channel fluid flow leading to the main energy loss of the rotor system. Moreover, operating at a high rotational speed can cause cavitation near the blades which may jeopardize the propulsion efficiency and induce noise. In order to effectively improve the propulsion efficiency of the pump-jet propeller, it is mandatory to research more about the energy loss mechanism in the tip clearance area. Due to the complex turbulence characteristics of the blade tip vortex, the widely used Reynolds averaged Navier–Stokes (RANS) method may not be able to accurately predict the multi-scale turbulent flow in the tip clearance. In this paper, an unsteady numerical simulation was conducted on the three-dimensional full flow field of a pump-jet propeller based on the DES (detached-eddy-simulation) turbulence model and the Z-G-B (Zwart–Gerber–Belamri) cavitation model. The simulation yielded the vortex shape and dynamic characteristics of the vortex core and the surrounding flow field in the tip clearance area. After cavitation occurred, the influence of cavitation bubbles on tip vortices was also studied. The results revealed two kinds of vortices in the tip clearance area, namely tip leakage vortex (TLV) and tip separation vortex (TSV). Slight cavitation at J = 1.02 led to low-frequency and high-frequency pulsation in the TLV vortex core. This occurrence of cavitation promotes the expansion and contraction of the tip vortex. Further, when the advance ratio changes into J = 0.73, a third type of vortex located between TLV and TSV appeared at the trailing edge which runs through the entire rotational cycle. This study has presented the dynamic characteristics of tip vortex including the relationship between cavitation bubbles and TLV inside the pump-jet propeller, which may provide a reference for the optimal design of future pump-jet propellers.